Marketing Strategy and Problems of Furniture Enterprises in Greater Jakarta Area - Darwin Simanjuntak (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2021)
This study aimed to determine the marketing practices and problems of the furniture enterprises in Greater Jakarta Area. This study uses the descriptive method of research. Data was obtained by using a questionnaire and followed by interview to obtain the further opinion of the respondents. The very core problems of the study are to determine the marketing practices and strategies of the furniture enterprises. Living room sets, dining room sets, bedroom furnishings, and chairs are type of products produced. Quality of product, good design and durabilty are the product attribute desired by the buyers. USA, Germany, Netherlands, UK, and Japan as a major export destinations. Participation in traade fair, correspondence, website &instragram are most common method of introducing product to the market. Full cost plus mark-up, manufacturing cost plus mark-up are common pricing practices of furniture firms. The firms placed high premium on maximizing profit and increase market share, mark-up pricing and target return pricing are the common pricing strategies of furniture firms, participation in trade fair, placing website & instragram are the most common promotion mix employed by furniture firms. Musrooming of new producers for the local market is a threat that affect local furniture firms, limited involment in trade fair, lack of market information and unpredictable demand are the nature of problem encountered, high tax and interest rate, increse of manpower wage rateswere the most severe problems.Trade fair subsidy, modern machinery subsidy, favorable tax rate dan reduce minimum wage rate are the expect assistance program from the government. Key words: Marketing Practices and Problems, Government Assistances Program, Furniture enterprises.